2022
DOI: 10.1101/2022.10.27.513965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical force induces DRP1-dependent asymmetrical mitochondrial fission for quality control

Abstract: Mitochondria are membrane-bound organelles that perform diverse critical biological functions. They undergo constant fission and fusion, which are important for mitochondrial inheritance, functions, and quality control. While tremendous efforts have identified many factors governing mitochondria dynamics, emerging evidence indicates the involvement of various intracellular or extracellular mechanical cues. However, how mechanical stress directly modulates mitochondrial dynamics remains largely unknown. Here ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In particular, the microtubule‐based motor proteins dynein and kinesin move mitochondria along microtubule tracks and deliver piconewton forces which induce tension on mitochondrial membranes (Howard, 2002; Xie & Minc, 2020). Moreover, recruiting molecular motors to the outer mitochondrial membrane via an optogenetic approach induces membrane deformation and pulls membrane tubules which systematically undergo DRP1‐dependent and ER‐dependent fission (Liu et al., 2022; Song et al., 2022). The mechanisms underlying the preferential fission at the protruding tubules are not yet clear.…”
Section: Mechanical Cues and Alterations In Mitochondrial Mechanical ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the microtubule‐based motor proteins dynein and kinesin move mitochondria along microtubule tracks and deliver piconewton forces which induce tension on mitochondrial membranes (Howard, 2002; Xie & Minc, 2020). Moreover, recruiting molecular motors to the outer mitochondrial membrane via an optogenetic approach induces membrane deformation and pulls membrane tubules which systematically undergo DRP1‐dependent and ER‐dependent fission (Liu et al., 2022; Song et al., 2022). The mechanisms underlying the preferential fission at the protruding tubules are not yet clear.…”
Section: Mechanical Cues and Alterations In Mitochondrial Mechanical ...mentioning
confidence: 99%
“…The mechanisms underlying the preferential fission at the protruding tubules are not yet clear. On one hand, there is a higher probability that long mitochondrial tubules reach the ER and form contact sites (Liu et al., 2022). On the other hand, mitochondrial tubules, which are thinner than the mitochondrial body diameter, have a higher local membrane curvature and may provide preferential fission sites by recruiting the fission machinery.…”
Section: Mechanical Cues and Alterations In Mitochondrial Mechanical ...mentioning
confidence: 99%
“…Knots are observed more frequently with longer/more nanotubes, both of which are modulated by deflations. Membrane tubule contact is ubiquitous in eukaryotic cells, it was shown that ER tubules may entangle with mitochondria (membrane-bound organelles) fission sites mediating membrane transformation ultimately leading to mitochondrial division ( 41 , 42 ). The nanotube knots in our study are reminiscent of this complex network of membrane tubules and could potentially indicate further nanotube elongation and fission.…”
Section: Resultsmentioning
confidence: 99%